PENYIMPANGAN GRAMATIKAL DALAM BERITA SURAT KABAR TRIBUN TIMUR, FAJAR (MAKASSAR), DAN REPUBLIKA (JAKARTA) - NFN Herianah (Multilingual, 2013)
Indonesian language has been used as a means of expression and communication in the human activities, such as culture, science, and technology. Along with the times, they evolve as well as Indonesian language. In the Indonesian language development, the print media of ewspapers are still a lot of deviations. The method used in this writing is a qualitative descriptive method by using reading-listening, and noting. The results showed some eviations which was found in the various aspects like morphological, spelling, diction, and foreign-term deviations.